Biomass functions for mountain birch in the Vuoskojärvi Integrated Monitoring area - Starr, M.; Hartman, M.; Kinnunen, T. (Boreal Environment Research Publishing Board, 2024)
Simple linear regression models for estimating the oven-dry stem, living and dead branch, and leaf components of above-ground biomass for mountain birches (Betula pubescens ssp. czerepanovii, syn.: B. czerepanovii N.I. Orlova) taller than 1.3 m growing in the Vuoskojärvi Integrated Monitoring area are presented. The models were based on allometric relationships between biomass component and tree size characteristic: stump diameter (d0.1), breast height diameter (d1.3) and height (h) of 20 specimens. Correlation analysis indicated that d1.3 and d1.32h were the best variables explaining biomass. Logarithm (natural) transformation of both d1.3 and biomass component resulted in higher correlation coefficients. The linear regression model describing the relationship between ln(d1.3) and ln(biomass) of each component was highly significant (p < 0.0001) with R2 values ranging from 62% (dead branches) to 98% (stem). Using ln(d1.32h) did not notably improve the models. The stand above-ground biomass for a plot where all stems had been measured in 1995 was estimated at 21.2 t ha–1 (stems 61%, live branches 29%, dead branches 2% and leaves 8%).